Estudo analítico experimental de um conjunto gaseificador - MORAES, Sinfrônio Brito (Universidade Estadual de Campinas, 2018)
The research subject proposed in this study is based on an examination of the parameters significant for the process of ascendent and counter-current gasification. The gasifier which was utilized was a module proto type. The lower module has an extenal diameter of 50 cm and an internail diameter of 42 cm, owing to the refractory and to the double walls designed for the heating of the incoming air. The upper module with an external diameter of 55 cm and an internal diameter of 50,6 cm, is similarly made of double walls in view of the extraction of gas being localized at different The two modules are joined to each other in such a way as to enable a variation in the height of the charging of the gasifier, as well as in the height of the outgoing gas. The process of gasification used in the study was that of air gas or low-BTU gas. The study was divided into two geometries by varying be tween them, the relation of the height of the outgoing gas and the diameter of the gasifier. When gas was extracted by the upper perforation with a relation δ = 3,09 it is denominated upper geometry andwhen δ=214, lower geometry. Five experimento involving different escapes of air were made for each of the geometries. Temperatus were measured at three different points of the gasifier in order to ascertain the behavior of the reaction zones according to the temperatures. The flows of air, gas, gasified coal and steam contained in the air were measured so that the analyses were made in terms of dimensional parameters. The composition of the gas was analyses chromografically in all the experiments undertaken, so as to determine the calorific potential of the gas, the percent of energy in each component of the resultant mixed gas, and the calorific power of the gasifier. In relation to the composition of air gas, the gasification behaved as if it were a mixture of water gas, owing to local ambiental condition. The composition presented, on analysis, parts of hydrogen and methane, thus contributing to an increase in the heating power of the gas and consequently, an increase in the heating potential of the gasifier.